Effect of technological innovation and diffusion on the interindustry mobility of Brazilian workers - Juliana Gonçalves Taveira; Eduardo Gonçalves; Ricardo da Silva Freguglia (EconomiA, 2014)
This paper aims to investigate the effects of investment in industrial R & D on the mobility of workers between firms and/or industrial sectors in Brazil, considering that the technological gap between the sectors can reduce the propensity for interindustrial labor mobility. Using panel data for the period 2003–2008, constructed from microdata RAIS-Migra and industry data from the Brazilian Technological Innovation Survey (PINTEC), the Annual Industrial Survey (PIA) and input–output matrices, we estimate a multinomial logit model with random intercepts (GLLAMM – Generalized Linear Latent and Mixed Models). The main results show that the technological diffusion increases the chances of changing jobs, the technological variables have greater importance for unskilled workers than for skilled, and among non-intensive technology industries, the technological innovation can have positive impact on interindustrial mobility. – – Esse artigo tem por objetivo investigar os efeitos do investimento em P&D industrial sobre a mobilidade de trabalhadores entre firmas e setores industriais brasileiros, considerando que a distância tecnológica entre os setores pode reduzir a propens\~ao à mobilidade intersetorial de trabalhadores. Com o uso de um painel de dados para o período de 2003–2008, construído a partir de microdados da RAIS-Migra e de dados setoriais provenientes da Pesquisa de Inovaç\~ao Tecnológica (PINTEC), da Pesquisa Industrial Anual (PIA) e de matrizes de insumo-produto estimou-se o modelo logit multinomial com interceptos aleatórios (GLLAMM - Generalized Linear Latent and Mixed Models). Os principais resultados obtidos mostram que: a difus\~ao tecnológica aumenta as chances de mudança de emprego; variáveis tecnológicas possuem maior importância para os trabalhadores n\~ao qualificados do que para os qualificados; e, entre os setores n\~ao intensivos em tecnologia, uma inovaç\~ao pode ter impacto positivo sobre a mobilidade intersetorial.
Keywords: 330; Technological innovation; Technological diffusion; Mobility of workers; Multinomial logit; GLLAMM